ANALISA KINERJA KEUANGAN PERUSAHAAN TELEKOMUNIKASI YANG TERDAFTAR PADA BEI MELALUI RASIO LIKUIDITAS, SOLVABILITAS DAN PROFITABILITAS - Resti Setyaningsih; Burhanudin Burhanudin; Ida Aryati (JURNAL ILMIAH EDUNOMIKA, 2019)
The success of a company is determined by good financial performance. Company performance assessment can be determined by calculating financial ratios through financial statements. This research was conducted to determine the financial performance of Telecommunications companies listed on the Stock Exchange using liquidity, solvency and profitability ratios. This study uses secondary data, with data collection techniques, namely documentation and literature. The results of the ratio calculation show that the average financial performance of the company is in good condition, even though one company has a poor performance. Keywords : financial performance, financial ratios, financial statements